Copycat - Thomas, Adèle (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
An exchange programme involving students and academics from Egoli University in Johannesburg and the University of Athens provides the conduit for the smuggling of Venetian Grossi coins discovered on the Cycladic island of Naxos. Thirty-five year old Delancey James, a Professor of Ethics at Egoli University, stumbles upon events associated with the murder of a post-graduate student. Through her investigation, she uncovers a web of intrigue that links the coin smuggling to corruption at the highest levels of the University, and, in the process, her life is placed in mortal danger.
Keywords: Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Fiction; South African fiction (English) -- Study and teaching (Higher); South African fiction (English) -- 21st century